Rhodium–Cobalt Alloy Nanotubes Toward Methanol Oxidation Reaction. Issue 8 (4th May 2022) - Ding, Yu; Miao, Bo-Qiang; Liu, Ya-Chong; Hou, Nan; Yang, Yun; Jin, Pu-Jun; Yin, Shi-Bin; Chen, Yu
Abstract : The sluggish reaction kinetics of the anodic methanol oxidation reaction (MOR) seriously hinders the commercial development of direct methanol fuel cells. Considering the vital role of catalysts, this work focuses on the synthesis of rhodium–cobalt alloy nanotubes (RhCo‐NTs) through a simple one‐pot reduction approach using hydrazine hydrate as a reducing agent. RhCo‐NTs with different Rh/Co atomic ratios can be handily achieved by simply controlling Rh III /Co II feeding proportions. The hollow and tubular architecture of RhCo‐NTs gains abundant boundary/defect atoms, improves the atomic utilization of Rh, and enlarges the valid connection between active sites and reactants. Compared with commercial Rh nanocrystals, RhCo‐NTs with optimized Rh/Co atomic ratio show sharply enhanced MOR electroactivity and long‐term stability because of the particular tubular morphology, big electrochemical active area, suitable Co introduction, excellent self‐stability, and eminent anti‐poison capability. Abstract : Rhodium–cobalt alloy nanotubes (RhCo‐NTs) are obtained by a simple one‐pot reduction approach. Profiting from the abundant boundary/defect atoms, high atomic utilization of Rh, and the valid connection between active sites/reactant of hollow‐tubular architecture and electronic structure regulation of Co on Rh, RhCo‐NTs shows sharply enhanced methanol oxidation reaction (MOR) electroactivity and long‐term stability compared with commercial Rh nanocrystals.